2020
DOI: 10.7554/elife.54659
|View full text |Cite
|
Sign up to set email alerts
|

Osterix-Cre marks distinct subsets of CD45- and CD45+ stromal populations in extra-skeletal tumors with pro-tumorigenic characteristics

Abstract: Cancer-associated fibroblasts (CAFs) are a heterogeneous population of mesenchymal cells supporting tumor progression, whose origin remains to be fully elucidated. Osterix (Osx) is a marker of osteogenic differentiation, expressed in skeletal progenitor stem cells and bone-forming osteoblasts. We report Osx expression in CAFs and by using Osx-cre;TdTomato reporter mice we confirm the presence and pro-tumorigenic function of TdTOSX+ cells in extra-skeletal tumors. Surprisingly, only a minority of TdTOSX+ cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 58 publications
4
12
1
Order By: Relevance
“…Cells with osteogenic capacity are present in the circulation of animals and humans [51] , and recent data suggest that circulating osteocalcin positive cells may represent an early marker of bone metastasis [52] . In related work with other collaborators, we also find Osx+ cells in peripheral blood, but these cells are hematopoietic in origin [41] , [42] , and ontogenetically unrelated to the tumor associated TdT Osx + cells described here, which were selected for not expressing CD45. In fact, our transcriptomic analysis show that relative to the TdT Osx – population, tumor associated TdT Osx + cells have a mesenchymal, osteogenic signature, as they up-regulate genes involved in collagen matrix production and processing, as well as osteoblast-specific markers.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Cells with osteogenic capacity are present in the circulation of animals and humans [51] , and recent data suggest that circulating osteocalcin positive cells may represent an early marker of bone metastasis [52] . In related work with other collaborators, we also find Osx+ cells in peripheral blood, but these cells are hematopoietic in origin [41] , [42] , and ontogenetically unrelated to the tumor associated TdT Osx + cells described here, which were selected for not expressing CD45. In fact, our transcriptomic analysis show that relative to the TdT Osx – population, tumor associated TdT Osx + cells have a mesenchymal, osteogenic signature, as they up-regulate genes involved in collagen matrix production and processing, as well as osteoblast-specific markers.…”
Section: Discussionsupporting
confidence: 70%
“…The larger subcutaneous tumor growth and the apparent increased severity of metastatic disease in cKO mice prompted us to ask whether Ncad deletion in extra-skeletal cells may be involved in modulating tumorigenesis. Indeed, in a parallel study using the Ai9:Osx-cre reporter mouse we found that a proportion of cells in the stromal component of tumors generated by subcutaneous inoculation of breast (BO1) and melanoma (B16-10) cells express red fluorescence (TdT Osx +) [41] , [42] . We confirmed the presence of TdT Osx + cells in the stromal component (GFP– CD45– population) of orthotropic BO1 tumors grown in either WTe mice or in Cdh2 cKO mice, with no significant differences between the two genotypes ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…FSP1-Cre (S100a4-Cre) [31] mice on a FVB/n background were a gift from Dr. Gregory Longmore [32]. Osx-Cre;TdT mice were generated by crossing the following lines from The Jackson Laboratory, USA: B6.Cg-Tg(Sp7-tTA,tetO-EGFP/Cre)1Amc/J (catalog #006361) and B6.Cg-Gt(ROSA)26Sor tm9(CAG-tdTomato)Hze /J (TdT) (catalog #007909) [33]. All parental lines were maintained separately due to strain differences.…”
Section: Micementioning
confidence: 99%
“…Both the Osx-Cre and FSP1-Cre drivers have been previously shown to have off-target effects outside of the mesenchymal lineage, most notably in cells of hematopoietic origin [32,33,44,45,47,48]. To this end, we assayed CD45 expression.…”
Section: Nt3 Tumors Share Markers Of Soft Tissue Sarcomasmentioning
confidence: 99%
See 1 more Smart Citation